Dicer-dependent endothelial microRNAs are necessary for postnatal angiogenesis - Suárez, Yajaira; Fernández-Hernando, Carlos; Yu, Jun; Gerber, Scott A; Harrison, Kenneth D; Pober, Jordan S; Iruela-Arispe, M. Luisa; Merkenschlager, Matthias; Sessa, William C (Proceedings of the National Academy of Sciences - PNAS, 2008)
Posttranscriptional gene regulation by microRNAs (miRNAs) is important for many aspects of development, homeostasis, and disease. Here, we show that reduction of endothelial miRNAs by cell-specific inactivation of Dicer, the terminal endonuclease responsible for the generation of miRNAs, reduces postnatal angiogenic response to a variety of stimuli, including exogenous VEGF, tumors, limb ischemia, and wound healing. Furthermore, VEGF regulated the expression of several miRNAs, including the up-regulation of components of the c-Myc oncogenic cluster miR-17-92. Transfection of endothelial cells with components of the miR-17-92 cluster, induced by VEGF treatment, rescued the induced expression of thrombospondin-1 and the defect in endothelial cell proliferation and morphogenesis initiated by the loss of Dicer. Thus, endothelial miRNAs regulate postnatal angiogenesis and VEGF induces the expression of miRNAs implicated in the regulation of an integrated angiogenic response.